2017
DOI: 10.1159/000458460
|View full text |Cite
|
Sign up to set email alerts
|

Update on Postnatal Steroids

Abstract: Antenatal steroid treatment to enhance fetal lung maturity and surfactant treatment to prevent or treat respiratory distress syndrome have been major advances in perinatal medicine in the past 40 years contributing to improved outcomes for preterm infants. Use of postnatal steroids to prevent or treat chronic lung disease in preterm infants has been less successful and associated with adverse neurodevelopmental outcomes. Although early (in the first week of life) postnatal steroid treatment facilitates earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 30 publications
1
47
0
3
Order By: Relevance
“…Breaking this cycle using systemic corticosteroids is possible, and there are now over 50 randomised controlled trials studying the risks and benefits of various corticosteroid regimens [133, 134]. Dexamethasone increases the chance of successful extubation and reduces BPD but at the expense of increased risk of neurodevelopmental sequelae if used in the first week [133, 135]. We previously recommended that the smallest effective dose should be used and only for babies at highest risk of BPD such as those who remain ventilator-dependent after 1–2 weeks.…”
Section: Strategiesmentioning
confidence: 99%
“…Breaking this cycle using systemic corticosteroids is possible, and there are now over 50 randomised controlled trials studying the risks and benefits of various corticosteroid regimens [133, 134]. Dexamethasone increases the chance of successful extubation and reduces BPD but at the expense of increased risk of neurodevelopmental sequelae if used in the first week [133, 135]. We previously recommended that the smallest effective dose should be used and only for babies at highest risk of BPD such as those who remain ventilator-dependent after 1–2 weeks.…”
Section: Strategiesmentioning
confidence: 99%
“…These two small studies used sequential analysis and appeared to show benefit as regards weaning from ventilation but apart from infection4 adverse effects were not reported. In the next decade or so high-dose dexamethasone was studied in many randomised trials given early (in the first week) to try to prevent BPD or later (after the first week) to treat it 6. Meta-analyses of randomised controlled trials (RCTS) showed that dexamethasone facilitated extubation from ventilation and reduced BPD, although adverse effects of hypertension, hyperglycaemia and growth failure were considered to be both tolerable and reversible on stopping steroids.…”
Section: Some Historical Aspectsmentioning
confidence: 99%
“…Comparison of the early and late dexamethasone Cochrane systematic reviews suggests that early treatment is more harmful than late as regards cerebral palsy and the outcome ‘abnormal CNS examination’ 6. In 2005, we proposed that the reason that early treatment was more harmful was related to the risk of developing BPD if untreated 10.…”
Section: Some Historical Aspectsmentioning
confidence: 99%
See 2 more Smart Citations